Association between prenatal care and peripartum and postpartum maternal obstetric complications. ENDES 2017 to 2019: Asociación entre el control prenatal y las complicaciones obstétricas maternas periparto y postparto. ENDES 2017 al 2019 - Méndez Pajares, Angela N. (2021)
Introduction: Obstetric complications are an important cause of maternal morbidity and mortality, with prenatal control (PNC) being a strategy for their adequate prevention and treatment. Objective: To determine the association between adequate CPN and peripartum and postpartum maternal obstetric complications. Methodology: Quantitative, observational, retrospective, cross-sectional and analytical study, based on information from the ENDES 2017-2019. Results: A sample of 41,803 mothers was analyzed, 21,0% and 28,7% had peripartum and postpartum complications respectively, furthermore, it was found that not having a quality NPC (PR = 1.20; 95% CI = 1.14-1.27), residing in metropolitan Lima (PR = 1,38; 95% CI = 1,27-1,49) or in the mountains (PR = 1,25; 95% CI = 1,18-1,33), belong to wealth quintile two (PR = 1,13; 95% CI = 1,04-1,22) or three (PR = 1,11; 95% CI = 1,03-1,20), having been attended only by qualified personnel (PR = 1,81; 95% CI = 1,33-2,48) and only in the public sector (PR = 1,48; 95% CI = 1,31-1,68) were associated with a greater possibility of peripartum complications. Not having a quality NPC (PR = 1,28; 95% CI = 1,22-1,33), residing in metropolitan Lima (PR = 1,12; 95% CI = 1,05-1,20) or in the mountains (PR = 1,06; 95% CI = 1,01-1,12), belong to wealth quintile two (PR = 1,13; 95% CI = 1,05-1,20) or three (PR = 1,12; 95% CI = 1,05-1,19) and having received NPC only in the public sector (PR = 1,28; 95% CI = 1,17-1,41) were associated with a greater possibility of postpartum complications. Conclusions: Within the adequate NPC, an association was found between the quality NPC and the peripartum and postpartum maternal obstetric complications.